Implementasi Metode Berbasis Proyek untuk Meningkatkan Minat Baca PAI Siswa Kelas VIII SMPN 1 Karawang Barat - Jamal lullail; Hapid Hardiansyah; Muhammad Abdul Aziz; Nur aini Farida; M. Makbul (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2024)
This study aims to enhance the reading interest of eighth-grade students at SMPN 1 Karawang Barat through the implementation of Project Based Learning (PBL) method combined with an Inquiry Oriented Classroom approach. The research was conducted in two cycles, where the first cycle utilized lecture method and educational technology, while the second cycle implemented case-based discussions. Data were collected through observations, interviews, and documentation. The findings reveal that interactive and varied teaching methods, including the use of technology such as interactive features and QR codes, significantly improved students' reading interest and learning motivation. In the first cycle, students' reading interest was recorded at 55%, which increased to over 84% in the second cycle. These findings indicate that project-based learning methods combined with technology can assist students in better understanding the material and enhance their overall learning motivation.